Product Heterogeneity, Intangible Barriers & Distance Decay: The effect of multiple dimensions of distance on trade across different product categories - Maureen Lankhuizen; Thomas de Graaff; Henri De Groot (European Regional Science Association (ERSA), 2012)
This paper empirically examines the heterogeneity in the effects of multiple dimensions of distance on trade across detailed product groups. Using finite mixture modelling on bilateral trade data at the 3-digit SITC level, we endogenously group product categories into an, a priori unknown, number of segments based on estimated coefficients of multiple dimensions of distance in the gravity equation. The paper contributes to the literature by offering a new classification of products into homogeneous groups. We find that distance decay functions in a gravity model of international trade at a disaggregate level reveal a complex process that involve location characteristics (comparative and natural advantages, demand patterns or preferences) as well as intrinsic sensitivity of trade to multiple dimensions of distance.
Keywords: F14; F21; F23; 330; bilateral trade; gravity models; cultural distance; institutions; product heterogeneity; finite mixture modelling